(untitled) (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: Residual neuromuscular blockade commonly occurs after laparoscopic abdominal surgery, impacting patient recovery and safety. This study aimed to identify factors associated with residual neuromuscular blockade when using rocuronium in laparoscopic procedures. Method: The researchers conducted a cross-sectional descriptive study on 92 patients undergoing laparoscopic surgery in the Department of Anesthesia and Resuscitation, Nguyen Tri Phuong Hospital. The residual neuromuscular blockade was monitored using the TOF (train of four) index with the TOF-watch nerve stimulator, a device used to monitor neuromuscular function, was applied at the time of extubation. Results: The incidence of residual neuromuscular blockade with rocuronium (TOF < 0.9) at the time of extubation following laparoscopic abdominal surgery was 53.3%, patients who did not receive prophylactic antibiotics had a higher rate of residual neuromuscular blockade compared to those who did (p<0.05). The duration of surgery was longer in patients with residual neuromuscular blockade, averaging 10 minutes more than those without residual blockade (p<0.0125). Additionally, the time from administration of the reversal agent to extubation was longer in patients with residual neuromuscular blockade, averaging 4 minutes more than those without residual blockade (p<0.015). Conclusion: The incidence of residual neuromuscular blockade with rocuronium following laparoscopic abdominal surgery is relatively high. There is a correlation between residual neuromuscular blockade and the use of prophylactic antibiotics, duration of surgery, and the time from administration of the reversal agent to extubation. It is essential to monitor, recognize, and assess the risk of residual neuromuscular blockade early to reduce the risks and complications associated with residual blockade and to improve the quality of patient recovery.